Affect of fatigue on activation strategy of muscles: SEMG study - Singh, V. P.; Kumar, D. K. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
This research aims to identify the neuromotor changes in muscles associated with fatigue during sprint cycling among 11 recreational cyclists who performed the WAT of 30s. The paper reports experiments conducted where changes in muscle recruitment strategies were studied using multiple recordings of SEMG of lower limb muscles and load was kept constant It is observed that near the end of such an exercise, there is a delay in activation / deactivation of the muscles. This causes the agonist muscles to do negative work during the upward part of the pedal cycle and reduces efficiency. It is suggested that if cyclists activated their muscles for shorter durations after they were fatigued, they may increase their output and reduce the stress on their muscles.